Oxygen Isotopic Composition of Drifting Snow in Mizhuho Plateau, East Antarctica (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Kikuo KATO; Okitsugu WATANABE; Kazuhide SATOW (National Institute of Polar Research, 1979)
Oxygen isotopic composition of drifting snow sampled at the various stations along the traverse routes in Mlzuho Plateau was determined, in order to investigate transportation of water vapor to Antarctic ice sheet resulting from the approach of a circumpolar cvclone. The oxygen isotopic composition of drifting snow in every season at the stations below 1800 m in altitude is largely controlled by the supply of ^O-rich water vapor resulting from the approach of a circumpolar cyclone, but it is not so at the stations above 2000 m. A large anomaly is found in the variation with altitude of oxygen isotopic comnosition of drifting snow at the stations at altitudes between 3100 and 3200 m, in (austral) spring. The area where the anomaly is found is the boundary between the spheres of influence of circumpolar cyclones and Antarctic anticyclones, and it changes its position seasonally. In winter, Mlzuho Station (2230 m in altitude) is considered to be hardly influenced by circumpolar cyclones